The Effect Of Psycoeducation Through Booklets On Parents' Knowledge About Children's Development In Kindergarten Plus Qurthuba - Novita Maulidya Djalal; Amalia Ramadhani; Nurhasanah, Nurhasanah; Nur Magfirah Muskiman (International Journal of Education, Vocational and Social Science, 2023)
Knowledge is a result of something through the senses of an object. Psychoeducation is a provision of information services to the public regarding various psychological knowledge or skills that play a role in dealing with various problems in everyday life. This study aims to determine the effect of psychoeducation through booklets on parents' knowledge about child development in Kindergarten Plus Qurthuba. The research method uses the One Group Design experimental method pre-test and post-test. There were 20 participants in this study. After cleaning the data, 15 participants survived and 5 participants fell. The results showed that there was an increase in the knowledge of parents of students in Kindergarten Plus Qurthuba about cognitive development, forms of intelligence, learning styles, and methods and time for memorizing children.